UTILIZING CHERNOFF FACES IN MODELING RESPONSES IN THE EVALUATION OF TRIMESTER SCHEME IMPLEMENTATION - Rosie C Lopez-Conde; Jenina N Nalipay; Inero V Ancho; Edna Luz R Abulon; Teresita T Rungduin; Ma. Antoinette C Montealegre; Jonathan A Madronero (Tạp chí Khoa học Đại học Đà Lạt)
This study uses Chernoff faces to model the responses of students, faculty, and administration staff of a teacher education institution in Manila, Philippines, to the implementation of an Outcomes-Based Teacher Education Curriculum (OBTEC) trimester scheme. Chernoff faces provide a valuable representation to model responses because people are used to studying and reacting to faces. This study used a quantitative research method by analyzing cross-sectional data from the study of the OBTEC trimester scheme. A total of 322 participants were selected through convenience sampling and given a 15-item survey in which possible responses ranged from 1 (strongly disagree) to 6 (strongly agree). The administrators were found to give a generally favorable rating (overall mean = 4.56 agree; overall SD = 0.45) to the OBTEC trimester scheme. The statements most highly rated by the administrators pertain to the success of OBTEC in integrating pedagogical content knowledge training with outcomes-based education, preparation of the students for the teaching profession, and consistency with the K to 12 curriculum. These responses are characterized by the structure of the face, the width of the mouth, and the height of the face, respectively. The most negative aspects of the OBTEC trimester scheme, according to the students, are characterized by hair height, nose width, and a hair style of thin hair that points downward. Chernoff faces were found to be a simple, yet powerful tool to model responses in the evaluation of the OBTEC trimester scheme.